The geochemical control of birnessite on selenium fate and transport at environmental concentrations - Szlamkowicz, Ilana B.; Ribeiro, Giovanna B.; Nguyen, Anna T.; Anagnostopoulos, Vasileios A. (Frontiers in Environmental Chemistry, 2025)
This study investigated the geochemical controls on selenium mobility by two forms of birnessite mineral, focusing on the influence of pH, concentration, and the presence of cations. The research aimed to understand the dominant reaction mechanism (redox vs. sorption) under environmentally relevant selenium concentrations. Experiments were conducted to study the interaction of selenium with the birnessite minerals under varying conditions. The results demonstrated a significant shift in the dominant reaction mechanism from slow redox reactions observed at artificially elevated selenium concentrations to fast sorption processes at environmentally relevant concentrations, with second order rates increasing from 7.63 x 10-7 to 0.0224 L mol-1 h-1, respectively. This finding highlights the crucial role of selenium concentration in determining its interaction with birnessite minerals and emphasizes the importance of conducting research under realistic conditions to accurately predict selenium mobility and develop effective remediation strategies.